1999
DOI: 10.1111/j.1574-6941.1999.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon source supply and its location on competition between inoculated and established bacterial strains in sterile soil microcosm

Abstract: The aim of this work was to study how the location of a carbon source and of bacterial cells in soil can enhance the growth of a bacterial inoculum. Studies were performed using irradiated soil and two pairs of strains of Bradyrhizobium japonicum and Pseudomonas fluorescens. For each species, an antibiotic‐resistant mutant was used as inoculant and introduced into a sterile soil pre‐colonised with its parent strain. The inocula and a glycerol amendment were introduced together or separately into soil using por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Indeed diffusion coefficients of glucose, fructose, sucrose and lactose in Ca-alginate membrane liquid-core capsules and in Ca-alginate beads immobilizing microorganisms were shown to be only 5-20% lower than the corresponding diffusivity in water [52,53] which explained why the concentration of solute in the bulk liquid medium reached equilibrium after a few minutes. The same conclusion was drawn by Duquenne et al [29] who suggested that diffusion of glycerol from microgranules to the soil limited the competitive advantage of such location effect. Conversely, skim milk remained in beads due to its chemical properties involving interactions with alginate.…”
Section: Co-location Of Carbon Substrates and Bacteria In Alginate Beadssupporting
confidence: 73%
See 1 more Smart Citation
“…Indeed diffusion coefficients of glucose, fructose, sucrose and lactose in Ca-alginate membrane liquid-core capsules and in Ca-alginate beads immobilizing microorganisms were shown to be only 5-20% lower than the corresponding diffusivity in water [52,53] which explained why the concentration of solute in the bulk liquid medium reached equilibrium after a few minutes. The same conclusion was drawn by Duquenne et al [29] who suggested that diffusion of glycerol from microgranules to the soil limited the competitive advantage of such location effect. Conversely, skim milk remained in beads due to its chemical properties involving interactions with alginate.…”
Section: Co-location Of Carbon Substrates and Bacteria In Alginate Beadssupporting
confidence: 73%
“…In this aim, immobilization of viable cells was shown by several authors as a convenient technique for improving their survival [13][14][15]. Also the location of substrate into the immobilization carrier can give a competitive advantage to the inoculated bacterium as already shown with glycerol and P. fluorescens immobilized cells in microgranules [29]. Likewise, we demonstrated in a previous work [11] the positive effect of cell immobilization in the maintenance of the siderophore activity in Fe-containing media.…”
Section: Co-location Of Carbon Substrates and Bacteria In Alginate Beadsmentioning
confidence: 77%
“…1c). Added glycerol might have diffused out of the carrier which would decrease the amount of substrate that could be used by the inoculant strain for its growth (Duquenne et al 1999). Significantly higher numbers of viable cells were enumerated from clay and rice bran + RP amended with 1% glucose than 0.1% (Fig.1e, f).…”
Section: Discussionmentioning
confidence: 98%
“…However, an appropriate formulation of microbial inocula requires further investigation. Indeed survival and consequently siderophore production can most likely be enhanced thanks to the supply of carbon substrates in the immobilization matrix (Duquenne et al, 1999), which could at the same time selectively promote immobilized cell growth and not indigenous microbial population in soil. Comparison of the siderophore production by free and immobilized cells of P. aeruginosa and P. fluorescens in the minimal medium by measuring the specific production of immobilized cells to their free counterpart ratio.…”
Section: Discussionmentioning
confidence: 99%